2007
DOI: 10.1677/joe-06-0172
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maternal undernutrition on the hypothalamic–pituitary–adrenal axis responsiveness in sheep at different ages postnatal

Abstract: Epidemiological and experimental data support the hypothesis of 'fetal programming', which proposes that alterations in fetal nutrition and endocrine status lead to permanent adaptations in fetal homeostatic mechanisms, producing long-term changes in physiology and determine susceptibility to later disease. Altered hypothalamic-pituitaryadrenal (HPA) axis function has been proposed to play an important role in programming of disease risk. The aim of the present study was to examine the effects of maternal nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 36 publications
2
37
0
2
Order By: Relevance
“…It has been established in many animals, from fish to birds and mammals, that maternal stress may influence the hypothalamicpituitary-adrenal axis of the offspring, resulting in altered behavioral development and/or ill thrift in the offspring for several months after birth. 2,8,13,16,17,36,45 In lizards, treatment of reproductive females or eggs with corticosterone can affect hatchling body size, growth rate, behavior (eg, dispersal and antipredator responses), and even sex. 52,66,68 Likewise, in crocodilians, limited studies suggest that high plasma corticosterone in females may result in relatively poor egg quality and decreased hatchling survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established in many animals, from fish to birds and mammals, that maternal stress may influence the hypothalamicpituitary-adrenal axis of the offspring, resulting in altered behavioral development and/or ill thrift in the offspring for several months after birth. 2,8,13,16,17,36,45 In lizards, treatment of reproductive females or eggs with corticosterone can affect hatchling body size, growth rate, behavior (eg, dispersal and antipredator responses), and even sex. 52,66,68 Likewise, in crocodilians, limited studies suggest that high plasma corticosterone in females may result in relatively poor egg quality and decreased hatchling survival.…”
Section: Discussionmentioning
confidence: 99%
“…Periconceptional undernutrition of sheep is reported to have only a minor influence on HPA axis function in their young adult offspring (15). In addition, the HPA axis can be reset by postnatal influences (16). A metaanalysis of human epidemiological studies reported an inverse association between birth weight and circulating cortisol level, although the majority of studies were underpowered.…”
Section: Hypothalamic-pituitary-adrenal (Hpa) Axis Hypothesismentioning
confidence: 99%
“…Adversity in early life can result in long-term changes in the HPA axis as a consequence of epigenetic modifications of key regulatory genes in rodents, sheep and humans (Weaver et al 2004, Oberlander et al 2008, Murgatroyd et al 2009, Stevens et al 2010, Zhang et al 2010, Grace et al 2011. It has previously been demonstrated in sheep that exposure to maternal undernutrition during the periconceptional period and early gestation results in altered fetal adrenal development from as early as 55 days of gestation (termZ150G3 days of gestation; MacLaughlin et al 2007), an earlier prepartum activation of the fetal HPA axis (Edwards & McMillen 2002b, Bloomfield et al 2004, an increased risk of premature delivery (Bloomfield et al 2003) and increased plasma cortisol concentrations in the post-natal lamb (Gardner et al 2006, Chadio et al 2007. We have also recently reported that exposure to dietary restriction during the periconceptional period in either normal-weight or overweight ewes using the same animals in the current study results in increased adrenal growth, a greater cortisol response to stress and a decrease in the adrenal expression and methylation levels of the imprinted gene, insulin-like growth factor 2 (IGF2) in the offspring (Zhang et al 2010).…”
Section: Introductionmentioning
confidence: 99%